2023
DOI: 10.1186/s12873-023-00840-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trauma-related emergency medical services during the COVID-19 lockdown in the Western Cape, South Africa

Abstract: Background To limit virus spread during the COVID pandemic, extensive measures were implemented around the world. In South Africa, these restrictions included alcohol and movement restrictions, factors previously linked to injury burden in the country. Consequently, reports from many countries, including South Africa, have shown a reduction in trauma presentations related to these restrictions. However, only few studies and none from Africa focus on the impact of the pandemic restrictions on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
0
1
Order By: Relevance
“…There was a greater percentage of gunshot wounds as a chief complaint, which is similar to findings reported by others [ 27 , 28 ]. However, Pettke et al found that in South Africa, assaults decreased during the strictest lockdown period, which is in contrast with our findings, reflecting a difference in patient populations [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…There was a greater percentage of gunshot wounds as a chief complaint, which is similar to findings reported by others [ 27 , 28 ]. However, Pettke et al found that in South Africa, assaults decreased during the strictest lockdown period, which is in contrast with our findings, reflecting a difference in patient populations [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%